2023
DOI: 10.1002/cjoc.202200688
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Polymethine Dyes for Near‐Infrared Organic Photodiodes

Abstract: Comprehensive Summary Near‐infrared organic photodiodes (NIR OPDs) have tremendous potential in industrial, military, and scientific applications, due to their unique features of lightweight, low toxicity, high structural flexibility, cooling‐system‐free, etc. However, the overall performance of currently available NIR OPDs still lags behind the commercial inorganic photodetectors, ascribed to the critical challenge of realizing organic semiconductors with sufficiently low optical bandgap and excellent optoele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 110 publications
0
7
0
Order By: Relevance
“…27,28 In this context, squaraine dyes (SQs) with a unique zwitterionic resonance D−A−D structure have shown great potential for NIR OPDs. 29,30 SQs can be synthesized via a facile condensation process and generally possess high molar absorption coefficients above 10 5 M −1 cm −1 in the NIR region. 31,32 Nonetheless, these dyes still suffer from uncontrolled aggregation in the solid state and relatively poor charge transport, limiting their potential application in NIR OPDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 In this context, squaraine dyes (SQs) with a unique zwitterionic resonance D−A−D structure have shown great potential for NIR OPDs. 29,30 SQs can be synthesized via a facile condensation process and generally possess high molar absorption coefficients above 10 5 M −1 cm −1 in the NIR region. 31,32 Nonetheless, these dyes still suffer from uncontrolled aggregation in the solid state and relatively poor charge transport, limiting their potential application in NIR OPDs.…”
Section: Introductionmentioning
confidence: 99%
“…To date, NIR OPDs have made considerable progress in terms of device performance, with the best responsivity approaching 0.6 A W –1 and the specific detectivity on the order of 10 12 (from direct experimental noise characteristics) and 10 13 (shot-noise-limited) Jones. However, most of the organic semiconductors have poor absorption capability in the NIR region and also suffer from the undesirable tail effect, which leads to strong exciton recombination and an increase in thermal effects. , Thus, development of novel narrow-band-gap organic semiconductors is urgent for improving the detection performance of OPDs in the NIR region. There are two mainstream molecular design strategies for narrowing the optical band gap of materials so far, i.e., quinoid resonance structure and donor–acceptor (D–A) structure. , In this context, squaraine dyes (SQs) with a unique zwitterionic resonance D–A–D structure have shown great potential for NIR OPDs. , SQs can be synthesized via a facile condensation process and generally possess high molar absorption coefficients above 10 5 M –1 cm –1 in the NIR region. , Nonetheless, these dyes still suffer from uncontrolled aggregation in the solid state and relatively poor charge transport, limiting their potential application in NIR OPDs. , To overcome the above challenges, Würthner et al recently reported an SQ-based J-type aggregate for narrowband NIR OPDs, showing a peak external quantum efficiency (EQE) of 12.3% at 1050 nm with a full-width at half-maximum (fwhm) of only 85 nm under zero bias . We have also shown that polymerization of SQs into conjugated polymers is a feasible design strategy, and the resulting carbazole-bridged pyrrolic polysquaraines can deliver impressive dark current densities ( J d ) as low as ≈2.0 × 10 –11 A cm –2 at zero voltage, leading to specific detectivity ( D *) values over 10 11 Jones at 860 nm in the self-powered mode …”
Section: Introductionmentioning
confidence: 99%
“…4,5,10,11,37−41 Recently, because their absorption range covers a substantial fraction of the solar spectrum, Cy5 and Cy7 dyes have also been developed for energy harvesting. 23,28 As polyene iminium chromophores, the cyanine dyes show substantial chemical reactivity. 5,13,20,42−45 Their degradation involving singlet oxygen has been investigated in recent decades, leading to novel insights and methods.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[29][30][31] Polymethine dyes have been continuously studied as one of the most conspicuous NIR NIR-absorbing materials, due to their intrinsic merits including simple synthesis, easily tunable structure, intense and narrow absorption in the NIR region, etc. [32][33][34] Among a variety of polymethines dyes, [35] squaraines (SQs) have shown much greater potential for the development of high-performance NIR OPDs than others, due to their unique zwitterionic donor-acceptor-donor (D-A-D) structure, wherein an electron-deficient cyclobutadiene core is end-capped by two electron-rich subunits. [36][37][38][39][40] Such structural features endow SQs with exceptional advantages over other polymethines, including high intrinsic photostability [41,42] and enhanced compatibility in bulk-heterojunction (BHJ) blends.…”
Section: Introductionmentioning
confidence: 99%